2021
DOI: 10.3390/ijms22105209
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Dysregulated Ion Transport and Mitochondrial Architecture as a Dangerous Liaison in Cancer

Abstract: Transport of ions and nutrients is a core mitochondrial function, without which there would be no mitochondrial metabolism and ATP production. Both ion homeostasis and mitochondrial phenotype undergo pervasive changes during cancer development, and both play key roles in driving the malignancy. However, the link between these events has been largely ignored. This review comprehensively summarizes and critically discusses the role of the reciprocal relationship between ion transport and mitochondria in crucial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 227 publications
(315 reference statements)
1
16
0
Order By: Relevance
“…Subplasmalemmal mitochondria buffer Ca 2+ movements during T cell activation [34], and ER-contacting mitochondria participate in Ca 2+ movements and lipid transfer [35]. Evidence indicates that a reciprocal relationship between dysregulated ion transport and mitochondria architecture may contribute to some cancers [36]. On the other hand, mito-nuclear communication has emerged as a new field of research to ascertain different crosstalk mechanisms between these organelles [37].…”
Section: Discussionmentioning
confidence: 99%
“…Subplasmalemmal mitochondria buffer Ca 2+ movements during T cell activation [34], and ER-contacting mitochondria participate in Ca 2+ movements and lipid transfer [35]. Evidence indicates that a reciprocal relationship between dysregulated ion transport and mitochondria architecture may contribute to some cancers [36]. On the other hand, mito-nuclear communication has emerged as a new field of research to ascertain different crosstalk mechanisms between these organelles [37].…”
Section: Discussionmentioning
confidence: 99%
“…30 Finally, some studies have confirmed that there are extensive changes in ion homeostasis and membrane potential during the development of cancer, which play a key role in the occurrence and development of malignant tumors. 31 The above evidence reveals that FHIT and neighboring genes might impact the occurrence and progression of LUAD and LUSC.…”
Section: Discussionmentioning
confidence: 90%
“…Mitochondria-targeted derivatives of TRAM-34 allow us to distinguish the pathophysiological roles of mitoK Ca 3.1 in cancer cells from those of the plasma membrane-located channel [ 81 ], since mitochondriotropic drugs reach the organelle within a few minutes [ 82 ]. We found that in contrast to the membrane-impermeant K Ca 3.1 inhibitor Maurotoxin [ 50 ], mitoTRAM-34 directly affected mitochondrial parameters such as membrane potential, ROS production, respiration, and morphology.…”
Section: Discussionmentioning
confidence: 99%